NCOG-30. MULTISESSION RADIOSURGERY FOR UNFAVORABLE NONFUNCTIONING PITUITARY MACROADENOMA: 5-YEAR OUTCOMES FROM A SINGLE INSTITUTION PROTOCOL. (14th November 2022) - Bhatnagar, Akrita; Carrasquilla, Michael; Nayar, Vikram; Collins, Brian; Collins, Sean; Anaizi, Amjad; Watson, Joseph; Jean, Walter C; Harris, Brent; Conroy, Dylan; Suy, Simeng; Ebadirad, Nelya; et al.
Abstract: Nonfunctioning macroadenoma is a commonly diagnosed pituitary tumor. Resection is the favored treatment, with radiosurgery often utilized for residual or progressing disease. Long-term outcomes are established for single-session radiosurgery, but mature outcomes are lacking for multisession radiosurgery. We report our institution's 5-year efficacy and safety results for unfavorable nonfunctioning pituitary macroadenoma patients treated with 5-fraction robotic radiosurgery. Between 2010-2020, patients who completed 5-fraction radiosurgery for the treatment of unfavorable nonfunctioning pituitary macroadenomas were included. A tumor was considered unfavorable if the gross tumor volume (GTV) was larger than 5 cc or if it closely approached a critical structure (optic apparatus, brainstem or pituitary gland). Local control was calculated using the Kaplan-Meier Method. RESULTS: Twenty predominately female patients (60%), age from 21-77 (median: 53 years) were included in this study. All underwent primary resection. Indications for radiosurgery included unresectable recurrence (85%) and residual disease progression (70%). Median tumor volume was 3.4 cm 3 (range: 0.3-20.8 cm 3 ) and 40% of the tumors were suprasellar. A mean dose of 30 Gy (range: 25Gy-30Gy), was delivered to a median isodose line of 80% (range: 75%-89%). Toxicity was minimal with 12 patients (40%) developing acute short-lived headaches and 1 patient (5%) developing a brief ipsilateral 6 th nerve palsy. There was no radiation induced optic or pituitary dysfunction identified in this cohort. At a median follow up of 5 years local control at 5 years was 95%. There was 1 in-field failure pathologically confirmed following surgery for pituitary tumor hemorrhage and 2 radiographically confirmed out-of-field failures in patients with large tumors (> 20 cc) treated with lower doses (25 Gy). CONCLUSIONS: The treatment of unfavorable nonfunctioning pituitary macroadenoma with 5-fraction robotic radiosurgery provides excellent local control to date, with minimal toxicity. Continued follow-up for the long term optic and pituitary function preservation and tumor control is needed.